IMPLEMENTASI KEBIJAKAN PELIMPAHAN SEBAGIAN KEWENANGAN BUPATI KEPADA CAMAT - Rustiari . (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The implementation of policies relating to the delegation of partial authority district to district, from 13 (thirteen) delegated areas not implemented well. The main purpose of this article to explains the implementation of delegating policy from head of district to head of subdistricts in Tenggarong. At the macro level policy of delegation of partial authority from the Head Regent to subdistrict particularly in Tenggarong can not run completely.